Decision on optimal airflow regulation solution set based on heat and airflow coupling characteristics of mine airflow in time series - Tong Jia; Heng Ma; Ke Gao (PLoS ONE, 2025)
Addressing the issue where traditional airflow regulation models, which treat natural ventilation pressure and ventilation resistance as constant values, fail to determine the optimal solution set for airflow regulation based on real-time dynamic mine environments, this research proposes a model based on the characteristics of airflow’s aerodynamic coupling with heat flow in an actual mine. A density-pressure-temperature characteristic equation is introduced to describe the variation laws of airflow state properties, forming a transient heat and airflow flow characteristics model in time series. Using the transient heat and airflow flow characteristics model as a correction variable, the fluctuating natural ventilation pressure and ventilation resistance model in time series is established. The fluctuating natural ventilation pressure and ventilation resistance are treated as environmental variables, and adjustment resistance is treated as a decision variable. A nonlinear correction airflow regulation model based on the heat and airflow coupling characteristics of airflow is constructed. This model is solved to obtain the optimal solution set for real-time airflow regulation, enabling precise airflow control. To verify the reliability of model, taking the Gucheng Coal Mine as an engineering research subject, An unsteady-state environmental field, which transfers energy to the airflow in a gradient flow field, is taken as the boundary condition. The unsteady-state heat transfer numerical model for the Gucheng Coal Mine is solved to analyze the heat and airflow coupling characteristics of airflow and to validate the proposed model. By inputting the heat environment time-series data of Gucheng Coal Mine into the transient heat and airflow flow characteristics model, the fluctuating natural ventilation pressure and ventilation resistance model, and the airflow regulation model, an optimal airflow control scheme is decided that meets the airflow requirements underground while minimizing system power consumption. The research provides a new theoretical foundation and methodological support for intelligent ventilation volume control in mines.